¿Rhinella achalensis en declinación? : Observaciones sobre el estado actual de las poblaciones del Sapo de Achala - Lescano, Julián Norberto (2018)
Sierras Pampeanas Centrales (SPC) mountains in central-western Argentina are inhabited by 30 species of amphibians. Four of them represent strict endemisms associated to high altitude grasslands and forests of the area. Rhinella achalensis is one of these species and is currently listed as Threatened and Near Threatened categories of the national and international species Red Lists, respectively. According to different studies developed in SPC, populations of R. achalensis have remained stable at least to the beginning of this century. In this work I present field data about the occurrence and current population status of R. achalensis in the SPC of Córdoba Province, compiled between 2007 and 2016. Occurrence and abundance of the Achala toad was assessed based on surveys done in 40 streams. Surveyed sites represented 67% of the historical localities known for the species from the literature. Populations of R. achalensis were found in 17.5% of surveyed streams, including three of eight surveyed historical localities. Besides, only 11 adults were found. The obtained results suggest that currently R. achalensis have small populations limited to small stream stretches. In contrast to previous works, the obtained results suggest that this species has declined. Some hypotheses about the factors potentially involved are postulated.